طوابع البرید التذکاریة المصریة عبر الحقب التاریخیة المختلفة کمصدر من مصادر المعلومات غیر التقلیدیة : دراسة ببلیومتریة - د. نها محمد عثمان (المجلة الدولية لعلوم المكتبات والمعلومات)
The commemorative stamp is a historical record of a state with all itsevents and important events over time. Therefore, it is an important source ofinformation that must be preserved and its historical, future and currentimportance highlighted.Over the years, Egyptian stamps will remain a memory that bearsEgyptian history with all its events, personalities and attitudes, and reflects thenature of the age for future generations.The Egyptian commemorative postage stamps are a record of the mostimportant events that Egypt has experienced, whether historical or militant, overthousands of years. It also commemorates the personalities who played a greatrole in Egypt's modern and contemporary history.The study aims at identifying the reality of Egyptian commemorativepostage stamps as a source of non-traditional information, and the numerical,qualitative and linguistic trends of these stamps. The study applied 1439 Egyptiancommemorative postage stamps. The descriptive analytical method was used.The bibliographic approach was used to study numerical trends And the quality ofEgyptian postage stamps.One of the most important results of the study is that the nature of thecommemorative postage stamp is an important source of non-traditionalinformation for information about ) the name of the country and the price of thestamp in Arabic only or in Arabic and English together, The name of a person, aparticular event, a particular occasion, or an institution. A small term may bewritten to describe a specific person or event. The name of the graphic designeror painter may be placed on a character, graphic design Design, symbol or formof a particular event, occasion or person, Sometimes watermarks or invisiblesignatures are placed in order to protect the character from imitation(The number of Egyptian commemorative stamps was also counted in1439 stamps from 1925 to 2017. The distribution of the stamps was calculatedaccording to the first and second deciles of the Dewey decimal classification. Theresearcher also classified the Egyptian postage stamps in another form, Whichcovers national and national events and events and national and internationalcelebrations and championships, came in first place with 29.1% with 419commemorative stamps. Second, we find the commemorative stamps coveringthe figures (national, scientific, artistic and religious) with 28.1% And the thirdplace, we find the commemorative stamps covering the achievements and  projects by 21.7% with 312 commemorative stamps. In the fourth place we findthe commemorative stamps that cover historical monuments and touristlandmarks by 17.9% with 257 commemorative stamps. Covers folk arts andcrafts. By 3.3% with 47 commemorative stamps.The Egyptian postage stamps were divided according to the dates of theirpublication to varying periods of time since 1925 - 2017.According to the language, Egyptian commemorative stamps, which werewritten in Arabic only, were equivalent to 1001 characters by 69.6%. Egyptianpostage stamps written in both Arabic and English were 360 characters with25.1% The Egyptian, written in both Arabic and French, understood 77characters by 5.4%. One Egyptian souvenir stamp was written in Arabic andRussian.